Distributive Justice - Aguiar González, Fernando (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This article offers a brief overview of the most influential theories of distributive justice, starting with John Rawls and ending up with Martha Nussbaum´s principles for a global justice. Along this way we will see how they answer these three questions: what to distribute, how it is distributed and among whom it is distributed. This will allow us to compare its foundations and principles of fair distribution, as well as to better understand its limits.